2015
DOI: 10.1002/2015jd023263
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and radiometric statistics on lightning flashes observed from space with the ISUAL spectrophotometer

Abstract: The Imager of Sprites and Upper Atmospheric Lightning (ISUAL) on the FORMOSAT-2 satellite was launched in 2004 and records transient luminous events (TLEs). ISUAL is an instrument composed of an imager and a multichannel spectrophotometer which is able to measure the brightness from far ultraviolet to near infrared for TLEs and lightning flashes. Several types of TLEs have been identified, classified, and documented between 2004 and 2014. However, no statistical analyses on lightning have already been realized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
9
1
Order By: Relevance
“…We assume a cloud top composition of water ice droplets with typical values r c = 15, 20 µm and n c = 2.5 × 10 8 m −3 (Dye et al, 2007;Ursi et al, 2019) while also accounting for the direction from the source to the detector relative to zenith. The altitude is estimated by assuming the cloud tops are at the tropopause (Splitt et al, 2010;Ursi et al, 2019) and that the tropopause altitude follows equation (2) of Offroy et al (2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume a cloud top composition of water ice droplets with typical values r c = 15, 20 µm and n c = 2.5 × 10 8 m −3 (Dye et al, 2007;Ursi et al, 2019) while also accounting for the direction from the source to the detector relative to zenith. The altitude is estimated by assuming the cloud tops are at the tropopause (Splitt et al, 2010;Ursi et al, 2019) and that the tropopause altitude follows equation (2) of Offroy et al (2015).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas only 12% of TGFs are associated with EIPs (Lyu et al, 2016), we find that almost all of them are followed by strong optical pulses and some with pre-activity starting many ms earlier (Figure 3d). The pulses have a higher blue-to-red ratio (Figure 3c) and longer durations than lightning without identified TGFs (Offroy et al, 2015;Christian & Goodman, 1987;Adachi et al, 2016), suggesting that they are a special type of current surge.…”
Section: Accepted Articlementioning
confidence: 91%
“…Based on previous studies, the absolute optical intensity from the first return strokes is on the order of 10 6 –10 9 W with a wavelength of 0.4–1.1 µm [ Guo and Krider, ]. Offroy et al [] and Kirkland et al [] showed that the median optical intensity of the return strokes is 2.5 × 10 8 W using satellite observation data from the ISUAL. Considering the difference in wavelength, the result indicates a reasonable agreement.…”
Section: Observations and Discussionmentioning
confidence: 99%
“…Using space‐ and ground‐based measurements, Kirkland et al [] showed that the pulse widths for return strokes, detected by the National Lightning Detection Network, are inversely proportional to pulse peak power. The Imager of Sprites and Upper Atmospheric Lightning (ISUAL) on the FORMOSAT‐2 satellite has also been used to observe TLEs and lightning emissions [ Adachi et al, , ; Frey et al, ; Offroy et al, ]. The system detects TLEs in the Earth's limb direction.…”
Section: Introductionmentioning
confidence: 99%
“…We assume a cloud top composition of water ice droplets with typical values r c = 15, 20 µm and n c = 2.5•10 8 m -3 (Dye et al, 2007;Ursi et al, 2019) while also accounting for the direction from the source to the detector relative to zenith. The altitude is estimated by assuming the cloud tops are at the tropopause (Splitt et al, 2010;Ursi et al, 2019) and that the tropopause altitude follows equation 2of Offroy et al (2015).…”
Section: Accepted Articlementioning
confidence: 99%